Ethnophysics Analysis of Traditional Patil Lele Game: Unveiling Physics Concepts in Local Wisdom - Rohmah, Azizatul Nur; Agustinaningrum, Nur Afni; Rohmah, Nur Lailatur; Sabrina, Nadya Mazayu Nur; Agustinur, Satya Cantika; Alemgadmi, Khalid Issa Khalifa; Deta, Utama Alan (International Journal of Research and Community Empowerment, 2024)
Local wisdom is integral to a community's cultural identity, encapsulating knowledge, values, and practices passed down through generations. The traditional game of Patil Lele, rich in cultural significance, also serves as a valuable educational tool for exploring fundamental physics concepts. This study aims to analyze the physics principles inherent in the Patil Lele game and identify optimal techniques for achieving maximum throwing distance. The research used a quantitative descriptive method; Data were collected through interviews and observations and supported by a thorough literature review. The findings reveal that the game embodies key physics concepts, including parabolic motion, Newton's laws, the moment of force, momentum, and impulse. Moreover, three effective techniques for enhancing throwing distance were identified. This research underscores the importance of applying physics concepts to enhance traditional games, enriching educational value and preserving cultural heritage.